Sublingual isosorbide dinitrate for the detection of obstruction in hypertrophic cardiomyopathy - Zemánek, David; Tomašov, Pavol; Homolová, Stanislava; Linhartová, Kateřina; Veselka, Josef (European journal of echocardiography, 2011)
AIMS: Hypertrophic cardiomyopathy (HCM) is predominantly associated with left ventricular outflow tract (LVOT) obstruction. The assessment of the obstruction with a provoking test should be a routine part of HCM evaluation. The aim of the study was to determine the utility of a sublingual spray application of isosorbide dinitrate (ISDN) for detection of an obstruction. METHODS AND RESULTS: We have prospectively analysed 77 consecutive HCM patients, measuring the LVOT gradient at rest, using the sublingual spray application of ISDN (2.5 mg; after 2, 5, and 10 min), and with exercise echocardiography. An obstruction was defined as a gradient ≥ 30 mmHg. An obstruction was present in 15 patients (19%) at rest, in 42 patients (55%) after ISDN, and in 55 patients (71%) after exercise. The ISDN test had a sensitivity of 76% and the specificity of 100% relative to exercise echocardiography, while at-rest measurements had a sensitivity of 27% and a specificity of 100%. The chronological difference in the prevalence of obstructions during the ISDN test was statistically significant (P < 0.05); at ISDN plus 2 min, obstructions were seen in only 29 patients (38%, gradient 28.8 ± 25.0 mmHg), however, at ISDN plus 5 and 10 min, obstructions were found in 42 patients (55%, gradient 44.5 ± 39.6 mmHg). CONCLUSION: The ISDN test is a reliable screening method for the detection of an HCM obstruction, however, the measurement should be delayed 5-10 min after the application of ISDN. Patients with negative ISDN tests should undergo exercise echocardiography.
Keywords: aplikace sublinguální; senzitivita a specificita; Administration, Sublingual; lidé středního věku; isosorbiddinitrát; lidé; Echocardiography, Stress; Vasodilator Agents; Cardiomyopathy, Hypertrophic; Middle Aged; zátěžový test; vazodilatancia; Female; Male; ženské pohlaví; Exercise Test; Isosorbide Dinitrate; Humans; Sensitivity and Specificity; mužské pohlaví; Ventricular Outflow Obstruction; obstrukce výtoku ze srdeční komory; zátěžová echokardiografie; hypertrofická kardiomyopatie